PERAN MEDIASI KUALITAS KETERHUBUNGAN DALAM PEMASARAN INTERNAL PERGURUAN TINGGI - Endi rekarti; Budi Suharjo; Rita Nurmalina; Setiadi Djohar (Universitas Mercu Buana, 2020)
Higher education institutions provide educational service that involves high intensity of interaction between lecturers and students. The relationship of a lecturer with the university determines the quality of the education that will be given to students. Exchanges that occur between lecturers and the higher education organizations, such as internal marketing activities, cannot be considered merely as a simple transactional economic process since educational role contains social elements in it. Relationship among university lecturers certainly plays an important role in determining lecturers' behavioral intention in conducting their academic tasks. This study is aimed to analyze the mediating role on the relationship quality of lecturers-college in marketing process where the effect of internal marketing offerings on Academic Behavioral Intention. With an online survey of 256 private university lecturers, this research seeks to analyze the magnitude of influence of the quality of Lecturer Connectivity on Academic Behavior Intention of lecturers. Data analysis was performed by utilizing Structural Equation Modeling with Lisrel software. Results have shown that the effect of the internal marketing mix towards Academic Behavioral Intention seemed to be greater through relationship quality in comparison to its direct influence.